Exploring the impact of imaging cadence on inferring CME kinematics - Vashishtha, Nitin; Majumdar, Satabdwa; Patel, Ritesh; Pant, Vaibhav; Banerjee, Dipankar (Frontiers in Astronomy and Space Sciences, 2023)
The kinematics of coronal mass ejections (CMEs) are crucial for understanding their initiation mechanism and predicting their impact on Earth and other planets. With most of the acceleration and deceleration occurring below 4 R ⊙ , capturing this phase is vital to better understand their initiation mechanism. Furthermore, the kinematics of CMEs in the inner corona (< 3 R ⊙ ) are closely related to their propagation in the outer corona and their eventual impact on Earth. Since the kinematics of CMEs are mainly probed using coronagraph data, it is crucial to investigate the impact of imaging cadence on the precision of data analysis and the conclusions drawn from it and also for determining the flexibility of designing observational campaigns with upcoming coronagraphs. This study investigates the impact of imaging cadence on the kinematics of ten CMEs observed by the K-Coronagraph of the Mauna Loa Solar Observatory. We manually track the CMEs using high cadence (15 s) white-light observations of K-Cor and vary the cadence as 30 s, 1 min, 2 min, and 5 min to study the impact of cadence on the kinematics. We also employed the bootstrapping method to estimate the confidence interval of the fitting parameters.Our results indicate that the average velocity of the CMEs does not have a high dependence on the imaging cadence, while the average acceleration shows significant dependence on the same, with the confidence interval showing significant shifts for the average acceleration for different cadences. The impact of degraded cadence is also seen in the estimation of the time of onset of acceleration. We further find that it is difficult to find an optimum cadence to study all CMEs, as it is also influenced by the pixel resolution of the instrument and the speed of the CME. However, except for very slow CMEs (speeds less than 300 Kms −1 ), our results indicate a cadence of 1 min to be reasonable for the study of their kinematics. The results of this work will be important in the planning of observational campaigns for the existing and upcoming missions that will observe the inner corona.